2007
DOI: 10.1097/01.fpc.0000236340.87540.e3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of polymorphisms in human cyclooxygenase-1 (PTGS1)

Abstract: Objective-Cyclooxygenase-1 (COX-1, PTGS1) catalyzes the conversion of arachidonic acid to prostaglandin H 2 , which is subsequently metabolized to various biologically active prostaglandins. We sought to identify and characterize the functional relevance of genetic polymorphisms in PTGS1.Methods-Sequence variations in human PTGS1 were identified by resequencing 92 healthy individuals (24 African, 24 Asian, 24 European/Caucasian, and 20 anonymous). Using site-directed mutagenesis and a baculovirus/insect cell e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…32 In humans, several COX genetic variants have been described, which potentially may account for inter-individual differences in pharmacological response to COX inhibitors. 33 A limitation to all retrospective twin analyses, including ours, is the potential for disease misclassification. This can significantly affect heritability estimates (see 13 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…32 In humans, several COX genetic variants have been described, which potentially may account for inter-individual differences in pharmacological response to COX inhibitors. 33 A limitation to all retrospective twin analyses, including ours, is the potential for disease misclassification. This can significantly affect heritability estimates (see 13 for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Because of reported linkage disequilibrium between the PTGS1 A–707G and P17L polymorphisms, we also examined whether PTGS1 diplotype contributed to aspirin response [13]. Thirty-nine (66%) subjects had the PTGS1 homozygous wild-type diplotype (–707AA and 17PP), 16 (27%) were heterozygous at either position –707 or 17 (–707AG or 17PL), and 4 (7%) were heterozygous at both positions (–707AG and 17PL).…”
Section: Resultsmentioning
confidence: 99%
“…Point mutations in the signal peptide region have been reported to disrupt the translocation and processing of various proteins [12]. In vitro studies have shown that platelets expressing the 17L variant are more susceptible to inhibition by indomethacin, another nonsteroidal anti-inflammatory drug [13]. The P17L SNP is in significant linkage disequilibrium with the A–707G SNP in the gene’s promoter region, and there are some data supporting an association between the A–707G SNP and antiplatelet response to aspirin [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is believed that the differences seen in the function of COX-1 most likely result from genetic variation in the regulatory or signal peptide region of the gene or from variation in platelet development and aging. Effects of such variation would hypothetically affect either the amount of COX-1 protein or the location of COX-1 protein in the cell (Halushka et al, 2003;Lee et al, 2007). COX-1 structure-function studies suggest that several amino acid substitutions with modest influence on arachidonic acid binding to the COX-1 active site can alter the catalytic efficiency and metabolite profile of COX-1-mediated arachidonic acid metabolism (Thuresson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%